What's So Social About Social Return on Investment? A Critique of Quantitative Social Accounting Approaches Drawing on Experiences of International Microfinance. (2nd January 2017) - Vik, Pål
ABSTRACT: Quantitative approaches figure prominently in social accounting and auditing. This is because of the preference among many investors for simple and ostensibly robust and comparative metrics. Social return on investment (SROI), which produces a monetised value for social impact generated per unit of currency invested, has emerged as one of the dominant tools to generate such metrics. This article discusses the merits of this increasing orientation towards quantitative metrics in social accounting using SROI as an exemplar and drawing on an extensive review of social impact evaluations in microfinance. The microfinance sector represents an interesting and relevant case for social accounting because it has been strongly orientated towards quantitative and experimental methods to evaluate its non-financial performance. The article concludes that, despite using sophisticated methods, the microfinance sector struggles to credibly determine its impact on customers. Self- and microfinance institution selection biases cast doubts on the merits of using national benchmark indicators or control groups. Consequently, it is argued that SROI is better viewed as a means of claiming symbolic legitimacy (as per [Luke, Belinda, Jo Barraket, and Robyn Eversole. 2013. "Measurement as Legitimacy Versus Legitimacy of Measures: Performance Evaluation of Social Enterprise." Qualitative Research in Accounting & Management 10 (3/4): 234–258. doi:10.1108/QRAM-08-2012-0034]) than as a robust method for evidencing social impact or a tool for managers and investors.